2001
DOI: 10.1074/jbc.m011741200
|View full text |Cite
|
Sign up to set email alerts
|

Sturgeon Orphanin, a Molecular “Fossil” That Bridges the Gap between the Opioids and Orphanin FQ/Nociceptin

Abstract: The elucidation of the cDNA sequence for sturgeon proorphanin provides a unique window for interpreting the evolutionary history of the opioid/orphanin gene family. The molecular "fossil" status of this precursor can be seen in several ancestral sequence characteristics that point to its origin as a duplication of either a prodynorphin-or proenkephalin-like gene. The sturgeon proorphanin cDNA encodes a precursor protein of 194 residues, and the orphanin heptadecapeptide itself binds not only the opioid recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…Research into the physiology of mammalian opioid ligand-receptor interactions has supported the idea of a strict functional dichotomy, in which the classic opioids interact with µ, and/or receptors to produce analgesia and nociceptin-ORL1 interactions act in an opposing fashion (Reinscheid et al 1998, Danielson et al 2001. Our results suggest that, in contrast to mammals, newts have ORL1 and opioid receptors that recognize both nociceptin and dynorphin.…”
Section: Figurecontrasting
confidence: 34%
See 1 more Smart Citation
“…Research into the physiology of mammalian opioid ligand-receptor interactions has supported the idea of a strict functional dichotomy, in which the classic opioids interact with µ, and/or receptors to produce analgesia and nociceptin-ORL1 interactions act in an opposing fashion (Reinscheid et al 1998, Danielson et al 2001. Our results suggest that, in contrast to mammals, newts have ORL1 and opioid receptors that recognize both nociceptin and dynorphin.…”
Section: Figurecontrasting
confidence: 34%
“…In mammals, nociceptin displays essentially no affinity for the canonical , and/or µ opioid receptors (Meunier et al 1995, Reinscheid et al 1995, Meng et al 1996, Pan et al 2002 and, despite a high degree of sequence homology shared among all of the opioid receptor classes, the ORL1 receptor in mammals does not recognize the classic opioid drugs that bind with high affinity to , and µ opioid receptors (Owens & Akil 2002). Such discrimination is especially interesting when it is appreciated that nociceptin (FGGFTGARK SARKLANQ) bears a significant degree of sequence identity to dynorphin A (YGGFLRRIRPKLKWDNQ) and belongs to the family of opioid peptides (Danielson et al 2001).…”
Section: Figurementioning
confidence: 99%
“…The sturgeon oFQ, with the N-terminal tyrosine, shows affinity for the mammalian ORL1 as well as the µ, , and opioid receptors. The authors suggest that the sturgeon oFQ represents an intermediate stage in the evolution of the proorphanin gene, and a ''transitional state in the eventual functional isolation of the orphanin heptadecapeptide from the classical opioids'' (Danielson et al 2001). If this is true, then receptor coevolution may have produced cognate receptor intermediates in some species capable of recognizing oFQ and the classical opioid peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the first complete non-mammalian vertebrate proorphanin cDNA gene sequence was obtained from the sturgeon, Acipencer transmontanus (Danielson et al 2001). The sturgeon oFQ peptide retains the classical opioid peptide core sequence (YGGF), whereas all mammalian oFQ peptides have a modified opioid-like core (FGGF).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous opioids (morphine-like substances) are also produced in tetrapods, which can suppress the intensity of pain experienced (Zieglgänsberger, 1986). A number of studies have shown that the nervous systems of teleost fish also produce chemical compounds related to adrenocorticotropic hormone and pain-mediating opiates (Ng and Chan, 1990;Vecino et al, 1992;Danielson et al, 2001). Jansen and Green (1970) and Ehrensing et al (1982) demonstrated that analgesia could be achieved in goldfish (Carassius auratus) subjected to electric shocks by adding morphine to the tank water.…”
Section: Central Integration Of Nociceptive Signals: Biochemical Medimentioning
confidence: 99%